Changes in endothelial nitric oxide synthase activity over time after induction of experimental diabetic retinopathy (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To examine changes in the activity of endothelial nitric oxide (NO) synthase in the development of endothelial dysfunction in experimental diabetic retinopathy corrected by various methods.Material and Methods: Albino (Wistar) rats (weight, 180-200 g) were used in this study and divided into 7 groups 60 animals each.Results: We found impaired endothelial function at day 30 of the experiment, and, subsequently, animals exhibited progression of pathological changes. Hypoglycemic agent only caused a mild, but not significant improvement in endothelial dysfunction, and did not allow restoration of normal synthesis of the proper amount of NO. Application of L-arginine and aflibercept in combination with hypoglycemic therapy for diabetic retinopathy led to repair of endothelial dysfunction and contributed to restoration of the physiological pathway for production of NO. Application of aflibercept and bromfenac in combination with hypoglycemic therapy for diabetic retinopathy led to a less pronounced effect than multi-component therapy including L-arginine, and this effect was not durable and significantly decreased by day 180. Application of aflibercept, L-carnitine and bromfenac in combination with hypoglycemic therapy showed more promising results than the above methods:  endothelial NO synthase (eNOS) activity increased at time point 1, and continued to increase subsequently, although normal values were not achieved.Conclusion: Aflibercept, L-arginine and citicoline in combination with hypoglycemic therapy was the most effective method among those tested in this study, with eNOS activity not only increasing as early as day 30, but also continuing to increase subsequently (days 60 and 180) and achieving normal values at day 180.
Keywords: experimental diabetic retinopathy; endothelial dysfunction; endothelial NO synthase; correction; metformin; aflibercept; L-arginine; citicoline; L-carnitine; bromfenac